Participation of T, B and NKT Lymphocytes and CD1 Molecule in the Infection by Entamoeba histolytica in Mice (Global Journal of Medical Research, 2015)
Studies have shown that CD1 double negative mice (CD1d -/-) develop larger liver abscesses due to their inability to present amebic antigens to NK T lymphocytes. Therefore, we conducted flow cytometry studies to determine the frequency of NK T, CD4 + T, CD8 + T and B lymphocytes in mice with amebic colitis. The frequency of NK T, CD8 + T and B lymphocytes was reduced in the MLN of mice in the CTRL-CD1 -/-and Eh-CD1 -/-groups compared to the CTRL-WT and Eh-WT groups. There was also a significant decrease in the frequency of B lymphocytes in the spleens of the animals in the Eh-WT group when compared with the CTRL-CD1 -/-, Eh-CD1 -/- and CTRL-WT groups. The results of the flow cytometry analysis highlight the importance of NK T lymphocytes in the immune response of mice to amebic intestinal infection and the importance of CD1 molecules in the activation of T and B lymphocytes.
Keywords: amebic colitis; Entamoeba histolytica; natural killer T lymphocytes